Study on the Motion Patterns of Nested Test Cabin and Its Shock Response Spectrum Analysis - Wei Wu; Wei Luo; Xing Liu; Jia Cui; Pengyu Zhang (IEEE Access)
This study investigates the motion patterns of the nested test cabin in a gunpowder gas overload test device. Multiple factors during the overload impact process were explored. Under the conditions of keeping the gunpowder combustion model, the friction coefficient between the inner and outer cabins, and the mass of the cabins unchanged, the special acceleration curve and its frequency spectrum and the impact response spectrum of the pseudo-velocity are analyzed. Numerical simulations and experimental studies revealed that there is compound motion between the inner and outer cabins in the gunpowder gas overload test device, resulting in small oscillations (referred to as oscillation wavelets) in the measurement results of the test system within the inner cabin. These oscillation wavelets occur when the critical acceleration of the test cabin reaches approximately 4700g. Increasing the initial velocity of the test cabin leads to a larger amplitude of the oscillation wavelets in the overall acceleration curve. In the frequency domain, secondary spectra appear under high overload conditions, and the bandwidth of the secondary spectra increases with the overload. The PVSRS trends for all overloads are roughly the same, with the variation in peak pseudo velocity being only on the order of $10^{-3}$ . Theoretical analysis and experimental results show good consistency, which helps to better understand the motion process of the test cabin in the gunpowder gas overload test device and provides support for the improvement and design of the overall device.